Impact of change in neighborhood racial/ethnic segregation on cardiovascular health in minority youth attending a park-based afterschool program. (May 2018) - D'Agostino, Emily M.; Patel, Hersila H.; Ahmed, Zafar; Hansen, Eric; Sunil Mathew, M.; Nardi, Maria I.; Messiah, Sarah E.
Abstract: Research on the mechanistic factors associating racial/ethnic residential segregation with health is needed to identify effective points of intervention to ultimately reduce health disparities in youth. We examined the association of changes in racial/ethnic segregation and cardiovascular health outcomes including body mass index percentile, sum of skinfold thicknesses, systolic and diastolic blood pressure percentile, and 400 m run time in non-Hispanic Black (NHB) and Hispanic youth (n = 2, 250, mean age 9.1 years, 54% male; 51% Hispanic, 49% NHB; 49% high area poverty; 25% obese) attending Fit2Play™, a multisite park-based afterschool program in Miami, Florida, USA. A series of crude and adjusted two-level longitudinal generalized linear mixed models with random intercepts for park effects were fit to assess the association of change in segregation between home and program/park site and cardiovascular health outcomes for youth who participated for up to two school years in Fit2Play™. After adjusting for individual-level factors (sex, age, time, and park-area poverty) models showed significantly greater improvements in cardiovascular health if youth attended Fit2Play™ in an area less segregated than their home area (p < 0.05 for all outcomes) except 400 m run time and diastolic blood pressure percentile in Hispanics (p<.001 and p = 0.11, respectively). Area poverty was not found to confound or significantly modify this association. These findings have implications for youth programming focused on reducing health disparities and improving cardiovascular outcomes in NHB and Hispanic youth, particularly in light of a continually expanding obesity epidemic in these groups. Parks and Recreation Departments have potential to expand geographic mobility for minorities, therein supporting the national effort to reduce health inequalities. Highlights: Reduced segregation was significantly associated with improved cardiovascular health. Minority youth had higher cardiovascular health benefits in more integrated areas. Area-poverty did not confound or modify the segregation-health relationship. Increasing geographic mobility in youth may promote cardiovascular health. Parks Departments may offer opportunities to reduce youth health disparities.